2013
DOI: 10.1007/s00431-013-2159-4
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome involving the face following snowball injury

Abstract: Complex regional pain syndrome (CRPS) is a condition of unknown etiology characterized by autonomic, sensory, and motor disturbance. CRPS usually follows an injury in the affected limb, which is often trivial in nature. CRPS involving the facial region is rare, and there have been no previous descriptions in children. We describe a 13-year-old girl with CRPS involving the face, which developed after being struck by a snowball. The clinical characteristics were similar to those of CRPS elsewhere in the body inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Goenka, et al, reported a 13-year-old girl, struck by a snowball, who developed facial CRPS. 3 Interestingly, she also had impairment of the left frontalis muscle as well as ptosis but retained full eye movement. In both cases, extensive investigations were undertaken before making the diagnosis because of the unusual location of CRPS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Goenka, et al, reported a 13-year-old girl, struck by a snowball, who developed facial CRPS. 3 Interestingly, she also had impairment of the left frontalis muscle as well as ptosis but retained full eye movement. In both cases, extensive investigations were undertaken before making the diagnosis because of the unusual location of CRPS.…”
Section: Discussionmentioning
confidence: 98%
“…This is the second reported case of pediatric facial CRPS. Goenka, et al ., reported a 13‐year‐old girl, struck by a snowball, who developed facial CRPS . Interestingly, she also had impairment of the left frontalis muscle as well as ptosis but retained full eye movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em Portugal são realizadas cerca de quarenta mil médias/grandes cirurgias reconstrutivas (Mendes & Figueiras, 2013), que apesar de ser desconhecida a sua etiologia, considera-se que por cada cem mil habitantes em Portugal, cento e trinta e sete pessoas sofrem de lesões na cabeça (Whitfield, 2009). De realçar que o trabalho multidisciplinar no desfiguramento facial adquirido ou congénito é consensual (Almeida et al, 2017;Baker, Owens, Stern, & Willmot, 2009;Braaf et al, 2016;Ewing-Cobbs et al, 2014;Ferraz-Torres et al, 2016;Goenka, Aziz, Riley, & Vassallo, 2014;Joseph et al, 2014;Kuhn et al, 2012;Linares, 2013;Masnari et al, 2012;Mendes, 2017;Zeytinoğlu et al, 2016), existindo a necessidade de programas de formação que permitam uma prevenção primária, no intuito de reduzir o impacto físico e psicológico da imagem corporal comprometida. Perante a evolução tecnológica, sugerem-se estratégias inovadoras educacionais que capacitem os indivíduos de conhecimentos e informações que se adaptem às suas necessidades (Landeiro et al, 2016).…”
Section: Considerações Finaisunclassified
“…A síndrome da ardência bucal é considerada uma dor neuropática não paroxística e contínua (Merskey e Bogduk, 1994;Siqueira e Teixeira, 2012). Por outro lado, há condições faciais crônicas complexas de critérios controversos, como a dor facial idiopática persistente (odontalgia atípica e/ou dor facial atípica) e a síndrome complexa de dor regional, podendo apresentar mecanismos variados e alterações sensitivas ao menos em parte dos doentes (De Seta, Mancini et al, 2014;Goenka, Aziz et al, 2014).…”
Section: Dor Facial Crônicaunclassified